Pengaruh Persepsi Profesi Tenaga Kependidikan Terhadap Minat Mahasiswa FKIP Menjadi Tenaga Kependidikan - Kamilah, Mauhibatul; Sulistyowati, Kharisma Putri; Hasanah, Uswatun (Journal of Character and ELementary Education, 2026)
The declining interest of students from the Faculty of Teacher Training and Education in pursuing careers as educational personnel had become an issue requiring serious attention. This condition was presumed to be influenced by students’ perceptions of the educational personnel profession. This study aimed to analyze the effect of perceptions of the educational personnel profession on students’ interest in choosing a career as educational personnel. The study employed a quantitative approach with an explanatory research design using a survey method. The sample consisted of 28 students from the Faculty of Teacher Training and Education at Universitas Sultan Ageng Tirtayasa, selected through stratified proportional random sampling. Data were collected using a Likert-scale questionnaire designed to measure students’ perceptions of the educational personnel profession and their career interests. Data analysis was conducted using simple linear regression. The findings indicated that perceptions of the educational personnel profession had a positive and significant effect on students’ interest in becoming educational personnel. The regression results showed that an increase in positive perceptions toward the profession was followed by an increase in students’ career interest. Furthermore, the analysis revealed that perceptions contributed meaningfully to variations in students’ interest, although other factors outside this study also influenced career decisions. This study concluded that strengthening positive perceptions of the educational personnel profession is essential for enhancing students’ interest in pursuing careers in the field of education.